2018
DOI: 10.1177/1357633x18775852
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient-centred home telehealth programme on outcomes in heart failure

Abstract: Background Telehealth is a promising intervention to reduce readmissions and healthcare-associated costs in patients with heart failure. Methods We performed a retrospective analysis of the impact of telehealth on 197 heart failure patients who had successfully completed one year of home telehealth monitoring following a heart failure admission as part of a clinically mandated programme at a Veterans Affairs Medical Center. Outcomes were compared both within the group (one year before and one year after home t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 18 publications
(28 reference statements)
2
32
0
Order By: Relevance
“…and home healthcare, to our knowledge, there has been little direct study of subsequent utilization after telehealth visits. [31][32][33][34] Gordon et al did a similar study in 2017 examining urgent care visits completed via telehealth vs. in-person care and found similar healthcare utilization for each modality after the initial visit, supporting our findings here. 35 This study adds value to the telehealth conversation because it examines subsequent care utilization after telehealth appointments, a key metric in the viability of telehealth in this setting.…”
Section: Discussionsupporting
confidence: 88%
“…and home healthcare, to our knowledge, there has been little direct study of subsequent utilization after telehealth visits. [31][32][33][34] Gordon et al did a similar study in 2017 examining urgent care visits completed via telehealth vs. in-person care and found similar healthcare utilization for each modality after the initial visit, supporting our findings here. 35 This study adds value to the telehealth conversation because it examines subsequent care utilization after telehealth appointments, a key metric in the viability of telehealth in this setting.…”
Section: Discussionsupporting
confidence: 88%
“…This increase in adoption is particularly important as some studies are beginning to suggest that video-telehealth consultations improve patient access to specialty care, decrease hospital J o u r n a l P r e -p r o o f admissions or emergency room visits, and possibly improve outcomes. 9,10 Some patients and clinicians who have used virtual video visits find them to be equivalent to in-person visits, without a perceived differential in the quality of care. 11,12 In a study from the Cleveland Clinic cardiac EP group, 60% of patients and nearly 70% of clinicians preferred to continue with virtual telehealth visits for further follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…Our results reveal a 40% reduction in the readmission rate by proactively targeting preventive intervention toward high-risk hospitalizations of home care patients. Previous studies also showed that a great portion of 30-day readmissions are avoidable through a series of resource-intensive interventions, including post-acute support, post-discharge monitoring [24], telehealth rehabilitation programs [25], and home care case management [26,27]. A readmission prediction model is of course the very first step to stratify patients and optimize resource utilization for home care patients.…”
Section: Discussionmentioning
confidence: 99%